2008
DOI: 10.1038/ncb1763
|View full text |Cite
|
Sign up to set email alerts
|

Actin and α-actinin orchestrate the assembly and maturation of nascent adhesions in a myosin II motor-independent manner

Abstract: Using two-colour imaging and high resolution TIRF microscopy, we investigated the assembly and maturation of nascent adhesions in migrating cells. We show that nascent adhesions assemble and are stable within the lamellipodium. The assembly is independent of myosin II but its rate is proportional to the protrusion rate and requires actin polymerization. At the lamellipodium back, the nascent adhesions either disassemble or mature through growth and elongation. Maturation occurs along an α-actinin–actin templat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

63
855
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 719 publications
(931 citation statements)
references
References 49 publications
63
855
2
2
Order By: Relevance
“…4 Although the cadherin-catenin complex is commonly described as the 'core' VE-cadherin complex, many other proteins can associate, such as scaffolding proteins and cytoskeletal regulators. 3,5 Some of these proteins, including vinculin, [6][7][8][9][10][11] epithelial protein lost in neoplasm (EPLIN) 12,13 a-actinin 14 and afadin, 15,16 have been found to bind to both a-catenin and actin and are therefore suggested to act as a link between the cadherin-catenin complex and actin. However, biochemical studies showed that a minimal cadherin-catenin complex consisting of E-cadherin, b-catenin and aE-catenin can directly bind to filamentous actin (F-actin).…”
Section: Introductionmentioning
confidence: 99%
“…4 Although the cadherin-catenin complex is commonly described as the 'core' VE-cadherin complex, many other proteins can associate, such as scaffolding proteins and cytoskeletal regulators. 3,5 Some of these proteins, including vinculin, [6][7][8][9][10][11] epithelial protein lost in neoplasm (EPLIN) 12,13 a-actinin 14 and afadin, 15,16 have been found to bind to both a-catenin and actin and are therefore suggested to act as a link between the cadherin-catenin complex and actin. However, biochemical studies showed that a minimal cadherin-catenin complex consisting of E-cadherin, b-catenin and aE-catenin can directly bind to filamentous actin (F-actin).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to cellular protrusions, initial binding of integrins to the ECM results in the integrin molecules clustering into focal complexes or nascent adhesions (Choi et al 2008) that can eventually mature into larger FAs or fibrillar adhesions . There are three different types of cell-matrix adhesions, namely, focal complexes/nascent adhesions, FAs and fibrillar adhesions, which have been so named due to their differing morphology, cell location and size ( Fig.…”
Section: Cellular Protrusions During Migrationmentioning
confidence: 99%
“…As a cell migrates, adhesion sites mature, beginning as small point contacts near the leading edge and developing to larger focal adhesions distal to the lamellipodia (Renaudin et al 1999;Rottner et al 1999). While the formation of nascent adhesions within the lamellipodium appears to be independent of myosin 2 activity (Choi et al 2008), maturation of these nascent sites, behind the lamellipodium, requires myosin 2 action. As part of the maturation process, focal adhesion kinase (FAK) (Bellis et al 1997) phosphorylates paxillin, the integrin assembly adaptor protein, on Tyr118, initiating active adhesion (Nakamura et al 2000;Tsubouchi et al 2002), a process involving conventional myosin activation.…”
Section: Adhesionmentioning
confidence: 99%